Profiles and Preferences of On-Line Millenial Shoppers in Bulgaria - Patricia R. Loubeau; Robert Jantzen; Elitsa Alexander (Economic Review: Journal of Economics and Business, 2014)
This research seeks to develop a better understanding of the factors affecting on-line purchasing behavior among Generation Y (Gen Y) consumers in Bulgaria. Also called millenials and born between the mid-1970s and late 1990s, this generation is especially active online and will be a dominant influence shaping e-commerce. An empirical study was conducted based on a written survey of a sample consisting of 367 high school and university students in Bulgaria. The most important reason why Bulgarian young people shop online is the pursuit of unique products not locally available, followed by convenience and better pricing, and their favorite category of internet purchases is "Apparel and Accessories." Bulgarian millennials are using the internet to shop for trendy fashion and to obtain a variety of brands that are unavailable locally. Like other regions of the world, concern about financial transactions security is a major barrier limiting the willingness to shop on-line in Bulgaria. Unlike other markets where online music purchases are growing, high levels of digital piracy in Bulgaria strongly discourage Bulgarian students from purchasing music online. One limitation of this study arises because of its reliance on a convenience sample of students from medium sized cities in Southern Bulgaria. Further research employing stratified random sampling across Bulgaria is needed to assess whether the findings are broadly generalizable for the Gen Y population.
Keywords: D12; 330; On-line shopping; Generation Y; consumer behaviour; Eastern Europe